Another University is Possible Otra universidad es posible - Luis Guillermo Barrantes Montero (Universidad Nacional, Costa Rica, 2013)
This paper proposes a way to be a University and to work as a University based on a new paradigm that responds to the demands of the 21st century society. After a brief overview of the traditional university models -as a way to illustrate, diachronically, the state of the situation of universities up to the currently prevailing model- a paradigm that is still in process is proposed: the transition from uni-versity to multi-diversity, through the integration of knowledge, development of critical thinking, and democratization of knowledge in order to reach common good Recibido 18 de abril de 2013 •  Corregido 16 de julio de 2013 • Aceptado 31 de julio de 2013 Se plantea un modo de ser y hacer universidad desde un nuevo paradigma, el cual deriva de las exigencias de las sociedades del siglo XXI. Luego de una breve sinopsis de los modelos tradicionales de universidad -con lo que se pretende ilustrar, de manera diacrónica, el estado de la situación de las universidades hasta llegar al modelo imperante en la actualidad-, se propone un paradigma que aún se encuentra en ciernes: el paso de la uni-versidad a la multi-diversidad, mediante la integración del conocimiento, el desarrollo del pensamiento crítico y la democratización del saber, con miras al bien común.